Olive Pomace in Diet Limits Lipid Peroxidation of Sausages from Cinta Senese Swine. Issue 1 (9th October 2017) - Serra, Andrea; Conte, Giuseppe; Giovannetti, Manuela; Casarosa, Laura; Agnolucci, Monica; Ciucci, Francesca; Palla, Michela; Bulleri, Eleonora; Cappucci, Alice; Servili, Maurizio; Mele, Marcello
Abstract : In order to examine whether olive pomace (OP), the mean by‐product of olive oil extraction, can be included in the animal diet, its effect on the raw mixture and sausages made from meat from OP‐fed Cinta Senese swine is tested by comparing it with a diet supplemented with high oleic sunflower oil (SO) and a control diet (C). Proximate composition, pH, color, total culturable bacteria, lactic acid bacteria (LAB), and lipid oxidation are evaluated in both the raw mixture and sausages. The aroma profile is also evaluated in sausages. Olive pomace affected the fatty acid composition of the raw mixture and strongly limited the lipid peroxidation of sausages, probably due to the synergistic action of 3, 4‐DHPEA and α‐tocopherol. Olive pomace selectively promotes LAB growth, and protected the raw mixture and sausages from discoloration. The diet also affected the content of volatile organic compounds thus enabling OP sausages to be distinguished from other sausages. Practical Applications: The protection of foods against lipid peroxidation is a very important aspect in terms of their quality. Achieving this naturally is a high priority for consumers, as there is an increasing demand for "low impact" and "environment‐safe" production processes. The approach proposed in the present study is aimed at meeting both these objectives. Our findings demonstrate that the inclusion of olive pomace in the swine diet effectively slowed down the lipid oxidation in the sausages. The strategy we propose also meets both economic and ecological goals. Olive pomace is the main by‐product of olive oil spinneret, and its re‐use in another spinneret is a cost‐effective way of improving the sustainability of the production process. Three different kinds of sausages are made. The experiment is aimed at studying the effect of olive pomace (OP) in controling the progression of lipid oxidation. OP have protected sausages against cholesterol oxidation, thus limiting the production of COPs (α‐hydroxycholesterol, α‐epoxycholesterol, and 7‐ketocholesterol). The most probable mechanism is attributable to electron or H+ donor properties of polyphenols contained in olive pomace. Abstract : Three different kinds of sausages are made. The experiment is aimed at studying the effect of olive pomace (OP) in controling the progression of lipid oxidation. OP have protected sausages against cholesterol oxidation, thus limiting the production of COPs (α‐hydroxycholesterol, α‐epoxycholesterol, and 7‐ketocholesterol). The most probable mechanism is attributable to electron or H+ donor properties of polyphenols contained in olive pomace.